The impact of tocilizumab on physical function and quality of life in patients with rheumatoid arthritis: a systematic literature review and interpretation - Townes SV (Dove Medical Press, 2012)
Shatara V Townes,1 Daniel E Furst,1 Anuradha Thenkondar21Department of Rheumatology, University of California-Los Angeles, Los Angeles, CA, USA; 2Sri Ramachandra Medical College and Research Institute, Chennai, IndiaObjective: To determine the impact of tocilizumab on physical function and quality of life in patients diagnosed with rheumatoid arthritis.Methods: A systematic literature review was performed to select for trials that could be used to examine the impact of tocilizumab on patients in terms of health-related physical function, quality of life, and quality of sleep. By examining background therapy, disease duration, and remission rates, we were able to determine the impact that a dose of tocilizumab has on various patients.Results: A total of 2617 tocilizumab-treated patients and 1271 controls were available for this study. Tocilizumab improved the Health Assessment Questionnaire Disability Index score statistically in comparison to the controls, with odds ratios from 1.4 to 7.0. Tocilizumab improved the physical function measure substantially more than the minimal clinically important difference (MCID) (5 units) – 8.9 and 9.7 – compared to 4.1 and 5.0 for controls. Seven and nine units of improvement were observed when measuring fatigue in rheumatoid arthritis patients. Using the Epworth Sleepiness Scale, we found that sleep improved (from 7.7 [3.1] to 3.4 [2.2]).Conclusion: Tocilizumab improves function and quality of life and decreases fatigue in patients with rheumatoid arthritis.Keywords: tocilizumab, rheumatoid arthritis, quality of life, sleep, randomized trials